The use of discourse markers in oral discourse in EFL classroom by pre-service EFL teachers - Kapranov, Oleksandr (Onomázein, 2020)
This article presents and discusses a computer-assisted case study of the use of discourse markers (further—‘DMs’) in oral discourse in English as a Foreign Language (EFL) by pre-service teachers in Norway. The aim of this case study is to explore the use of DMs by pre-service teachers (further referred to as ‘participants’) in EFL classroom by means of analysing the participants’ answers to the questionnaire that is designed to address the use of DMs in oral discourse in EFL after their school practice. The case study is informed by the view of DMs as “sequentially dependent elements that bracket units of talk” (Schiffrin, 1987: 31). The quantitative analysis of the participants’ questionnaires in statistical program SPSS version 18.0 (2009) indicates that the participants’ repertoire of DMs in their oral discourse in EFL classroom consists of such DMs as also, and, as, because, besides, but, especially, if, OK, or, so, and then. Additionally, the participants note that they do not use the following DMs during their teaching practice at school, e.g. indeed, moreover, and rather. These findings and their linguo-didactic implications will be further discussed in the article.